Perancangan Transportation Management System pada PT. X - Grace Natasha; Prayonne Adi (Jurnal Titra, 2021)
PT. X is a company that engaged in the production and distribution of motorbikes. This research was conducted in the LDD department, where the department supports the distribution process of motorcycle at PT. X. The role of the LDD department is to ensure the distribution process of motorbikes, so that motorbikes can reach the hands of consumers well. The LDD Department expects a working system that is more effective, efficient, and transparent in monitoring so that units that are not unfilled are low. Problems will be identified by using fishbone diagrams, where the results of the identification are found to be three main problems that occurs in the LDD department. The main problem is the opening of DO is not in accordance with the capacity of the truck, the truck does not come to take up the DO units that have been opened, and the trucks that come cannot be carried out the loading process directly. The improvements are made by digitizing the distribution process by Logistic 4.0 principle or designing the Transportation Management System (TMS). TMS is a system designed with the aim that the distribution process can be easily tracked and monitored. TMS will also connect related parties that previously sought manually. The distribution process is expected to be improved to be more effective, efficient and transparent